The founding of new firms and efficient decision-making structures in localized production networks. The example of television production in the Cologne media cluster (Germany) - Ivo Mossig (European Regional Science Association (ERSA), 2002)
Much literature often discusses localized production networks as possible engines of prosperous regional development. In this literature, vertical disintegration and corresponding further specialization of individual firms within a commodity chain is seen as an essential factor in the success of such localized production networks. Additionally, this literature emphasizes the importance of information intensive economic transactions and the resulting interdependence between complementary firms in the production network. In turn, this type of interdependence makes the specific, specialized competencies of a single firm available to other firms in the commodity chain. Furthermore, such a production system is regarded as highly flexible. Firstly, thanks to their specialization in a small subset of the production chain, the single enterprises are in a position to develop a wide range of special solutions in their field of production. As a result, they are able to react very quickly to changing and unstable market conditions. Secondly, there is an enormous flexibility and adaptability because of the production chain's frequent renewal. In extreme cases, a new chain is built specifically to meet the demands of a specific project and is dissolved after the project is completed. Thus, production could take place with almost completely new partners (i.e., firms) from one project to the next. The numerous interactions required to sustain the reorganization of production for each new project in turn depend on spatial proximity, trust and embeddedness within a common socio-institutional context. In turn, these features are further reasons for the success of such a production network. These regionally-anchored, flexibly-specialized networks are often called "industrial districts". These networks not only operate in small niches of certain industries, but are also found in some parts of the sevice sector. The proposed presentation analyses the decision structures operating inside the production network of TV-programs in Cologne's TV-production dominated Media-cluster. This research empirically confirms that competencies for decision-making are very unevenly distributed among the single units of the production chain. The research goes on to argue that the co-ordination of a highly disintegrated production network is possible only with a clear and plain hierarchy for decision making, execution and control processes. For this reason the network producing a TV-program is mainly designed and steered by only a handful actors. Although the competencies for decision-making are distributed unevenly through the production network, selection of subordinate partners by dominant firms is shaped by strong socio-institutional relations like trust based on previous positive working relations as well as common conventions, rules and routines. The final goal of the actual (December 2001) empirical research in Cologne is to analyse the decision-making structures affiliated with specific TV programs. This leads to a deeper understanding of how localized networks with uneven power structures work. In this context the question arises of how spatial concentration determines the respective decision-making process. At the same time there are still some indications that - besides some evolutionary factors - these special decision-making processes are a crucial factor in explaining the spatial concentration of TV-production in Cologne's Media Cluster.
Keywords: 330